Improving general practitioners' referral details of antidepressant use for patients referred for depression to primary mental health care: re-audit. (20th January 2015) - Towobola, A.; Cunningham, E.; Cotter, P.
Abstract : Background: This audit cycle looked at details of antidepressants given in general practitioners' (GPs) referral letters to Primary Mental Health Care (PMHC). With adequate information when patients are referred, time spent in clarifying details could be put into better use by clinicians and prompt effective treatment would help to reduce the direct and indirect costs of depression. Objective: To evaluate how effective our intervention was 7 months after a previous audit and identify areas that need improvement. Method: Audit of 33 referral letters of patients referred for depression from GPs to a PMHC service in Northern Ireland, followed by the intervention (feedback and pro forma ) and re-audit after 7 months. Results: The April audit showed 100% documentation of current antidepressant treatment and dose, but showed poor documentation of previous antidepressant use (33%), dose or duration (15%) and the reason for stopping the treatment (3%). Following intervention, the re-audit showed 25% and 24% rise in documenting previous antidepressant used and maximum dose reached, respectively, and 20% rise in documenting the reason for stopping. Conclusions: Our interventions made modest improvement in providing relevant data in referral letters. This study adds to the existing evidence that relying mainly on feedback as a method of implementing change is ineffective. Lack of enthusiasm for using the newly introduced pro forma suggests that mental health services should obtain more effective ways of engaging GPs in service development. Using a systematic approach, which includes identifying local barriers to change and providing a supportive environment are important before the next re-audit.